Prevalence of and factors influencing posttraumatic stress disorder among mothers of children under five in Kabul, Afghanistan, after decades of armed conflicts - Seino, Kaoruko (BioMed Central, 2008)
BACKGROUND: In the period following wars and other forms of armed conflict, health and quality of life of mothers is a major concern as they have the closest contact with children. The present study was performed to examine the impact of exposure to events related to armed conflicts on post traumatic stress disorder (PTSD) among women raising children, and to identify factors that alleviate the negative consequences of exposure to traumatic events. METHODS: A structured interview survey was conducted in Kabul Province, Afghanistan, in 2006. The subjects were the mothers of children less than 5 years old randomly selected from 1400 households in Kabul Province, Afghanistan. Symptoms of PTSD were assessed according to the criteria of Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition (DSM-IV). Exposure to traumatic events related to armed conflict, experience of hardship with regard to basic needs, resources that the subjects seek for mental health support, and socioeconomic variables were evaluated. Logistic regression analysis was performed to determine the association between PTSD symptoms and predictor variables. RESULTS: The prevalence rate of PTSD among 1172 women participated in this study was 29.8%. The most prevalent symptom was arousal (74.8%), followed by re-experiencing (54.9%) and avoidance (33.7%). The prevalence rate of PTSD symptoms among subjects who reported having experienced at least one event related to armed conflict (52.7%) was significantly higher than that among those who reported no such experiences (9.6%). Experience of food shortage was independently associated with PTSD. Seeking support for mental health was related to lower prevalence of PTSD symptoms among those who reported no direct experience of events related to armed conflict. However, no such relationship was observed with PTSD symptoms among those who reported having direct experience of events related to armed conflict. CONCLUSION: Direct exposure to traumatic events was significantly associated with PTSD symptoms among women raising children. For those who had experienced armed conflict-related events, food security mitigated the occurrence of PTSD symptoms; however, support seeking behavior did not show a significant mitigating influence on PTSD. Means to alleviate the negative influence of exposure to armed conflicts on the quality of life of women should be developed from the viewpoint of quality of mental health support and avoidance of material hardship.